The Essence of Costs in the Context of Enterprise Management Information Needs - Lazaryshyna, I. D.; Sluchak, V. O. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2024)
The aim of the article is to substantiate the essence of costs as a multifaceted economic category within the enterprise management system, to generalize approaches to their interpretation in the context of managerial information needs, as well as to identify transformational changes in the approaches to cost accounting and analysis under the influence of digital technologies, particularly cloud services. The article examines the essence of costs in the context of the information needs of enterprise management units and analyzes the evolution of approaches to defining costs: resource-based, economic, accounting, analytical, financial-monetary, socio-environmental, and managerial. It is demonstrated that the digital environment transforms not only the sources of cost formation but also the information requests of management units. It is substantiated that understanding the essence of costs and their interpretation in the conditions of digital transformation is essential for effective decision-making. Cloud technologies not only expand the functional capabilities of management but also require a new methodological approach to interpreting costs as an informational resource. A comparative analysis of approaches to defining costs has been conducted: resource-based, economic, accounting, analytical, financial-monetary, socio-environmental, and managerial. It is shown that the digital environment transforms not only the sources of cost formation but also the information requests of management units. A classification of information requests within the cost management system is proposed, taking into account the changes arising from the transition to cloud-based IT infrastructure. Modern cost management requires an expanded approach to interpreting costs as a multidimensional economic category. The implementation of cloud services necessitates the adaptation of accounting policies, modification of the cost information model, and improvement of methodological approaches to evaluating the effectiveness of managerial decisions in a digital environment. The prospects for further research are related to the development of unified approaches to accounting, analysis, and planning of costs associated with the digital transformation of enterprises.